Evaluasi tingkat keberhasilan reklamasi lahan bekas tambang timah di PT Timah Tbk - Nugrahani Trie Ryzzky; Yusni Ikhwan Siregar; Zulkarnain Zulkarnain (EcoNews, 2023)
PT Timah Tbk has operated tin mining for ± 45 years. The ratio between disturbed land reclaimed by PT Timah Tbk indicated a bad ratio. The study aims to analyze and evaluate the land reclamation of former tin mines in Air Jangkang Sinar Rembulan, Riding Panjang, Merawang, Bangka, Bangka Belitung Province. The reclamation is important to beneficial for the ecology, social and economic community. The research method used was an assessment of the success rate of reclamation based on a matrix that refers to Minister of Energy and Mineral Resources No. 1827 K/30/MEM/2018. The evaluation was done by comparing the plan and implementation data. Apparently, the overall reclamation is very good in that of backfilling 89%, spreading of top soil 93%, erosion and sedimentation 83%, planting 90%, acid mine water 92%, header closing 100% and maintenance 82%. Canopy cover mine 90%.